Ordered GeSi nanorings grown on patterned Si (001) substrates - Ma Yingjie; Cui Jian; Fan Yongliang; Zhong Zhenyang; Jiang Zuimin (Nanoscale Research Letters, 2011)
Abstract An easy approach to fabricate ordered pattern using nanosphere lithography and reactive iron etching technology was demonstrated. Long-range ordered GeSi nanorings with 430 nm period were grown on patterned Si (001) substrates by molecular beam epitaxy. The size and shape of rings were closely associated with the size of capped GeSi quantum dots and the Si capping processes. Statistical analysis on the lateral size distribution shows that the high growth temperature and the long-term annealing can improve the uniformity of nanorings. PACS code1·PACS code2·more Mathematics Subject Classification (2000) MSC code1·MSC code2·more